2019
DOI: 10.1097/qai.0000000000002051
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to PrEP Among Young Men Who Have Sex With Men Participating in a Sexual Health Services Demonstration Project in Alameda County, California

Abstract: Background: Young men of color who have sex with men face a continual increase in rates of HIV infection. Pre-exposure prophylaxis (PrEP) is an important prevention method for these young men. Setting: The Connecting Resources for Urban Sexual Health (CRUSH) demonstration project provided sexual health services, including PrEP, to young men who have sex with men aged 18–29 years. We report on adherence and factors influencing it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…25 The effectiveness of PrEP depends on its adherence, as pointed out by several studies. 11,14,26,27 Thus, it was found that most MSM adhered to it, considering the self-report of adherence, in the 30-day recall period, through the survey conducted in the first three clinical monitoring of the method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The effectiveness of PrEP depends on its adherence, as pointed out by several studies. 11,14,26,27 Thus, it was found that most MSM adhered to it, considering the self-report of adherence, in the 30-day recall period, through the survey conducted in the first three clinical monitoring of the method.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Increased adherence to PrEP among young MSM was also found in research by Myers and colleagues. 27 Besides, the high tolerability of the use of TDF/FTC by MSM should be noted. Adverse reactions are primarily of gastrointestinal tract origin and more prevalent at the beginning of use but usually decrease within one month of use.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth interview study participants were identified and selected from the cohort of youth who independently elected to use PrEP while enrolled in the CRUSH demonstration study. The CRUSH project eligibility criteria have been described elsewhere ( 3 ) but briefly included the following: ages 18 to 29, able to provide consent to participate in a research study in English or Spanish, and self-identified as “at-risk” for HIV infection. We employed a purposive sampling strategy with the intention of capturing a wide range of perspectives and experiences ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, advances in prevention and treatment coupled with a global commitment to end the epidemic have renewed our optimism for a future in which HIV infection is a rare occurrence. Pre-exposure prophylaxis (PrEP) in the form of a daily oral medication is highly effective at preventing HIV and is typically prescribed as part of a comprehensive package of services that includes routine HIV testing, counseling, and treatment for sexually transmitted infections as needed ( 3 , 4 ). HIV PrEP has been characterized as a revolution in HIV prevention and has the potential to advance the basic human rights of individuals through higher standards of sexual health ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral risk compensation also interests researchers [25,26], including risks of non-HIV sexually transmitted infections (STI) [27]. Prospective open-label cohorts ("demonstration projects") have identified heterogenous outcomes associated with PrEP use [28][29][30][31][32][33][34][35][36][37][38]. For example, reviews have shown that adherence can be associated with lower perceived stigma, greater empowerment, experiences of fewer side-effects, positive provider interactions, lower cost and less segmented health systems [39][40][41], that PrEP is associated with changes in condomless anal intercourse [42,43] and that STI incidence remains high in GBM taking PrEP [27,44,45].…”
Section: Introductionmentioning
confidence: 99%